2020
DOI: 10.1002/cam4.3625
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in receipt of standard chemoradiation in anal squamous cell carcinoma, an analysis of the National Cancer Database

Abstract: Background Standard treatment for locally advanced anal squamous cell carcinoma (SCC) consists of concurrent chemoradiation. We evaluated whether racial differences exist in the receipt of standard treatment and its association with survival. Methods From the National Cancer Database, we identified patients diagnosed with anal SCC (Stages 2–3) between 2004 and 2015. Using logistic regression, we evaluated racial differences in the probability of receiving standard chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…For instance, Hines et al observed colorectal cancer patients with stage II through IV tumors were at greater risk for receiving noncompliant care, attributing this to the additional need for neoadjuvant and adjuvant chemotherapy in stage II and III disease [17]. However, our results are consistent with other studies on ASCC, including those from Bian et al and Kole et al [16,42]. Bian et al performed a retrospective analysis of ASCC patients with stage II and III disease in the National Cancer Database (NCD) and found patients with stage III (as compared to lower stage II disease) and poorly differentiated or undifferentiated tumors were more likely to receive standard therapy [42].…”
Section: Discussionsupporting
confidence: 90%
“…For instance, Hines et al observed colorectal cancer patients with stage II through IV tumors were at greater risk for receiving noncompliant care, attributing this to the additional need for neoadjuvant and adjuvant chemotherapy in stage II and III disease [17]. However, our results are consistent with other studies on ASCC, including those from Bian et al and Kole et al [16,42]. Bian et al performed a retrospective analysis of ASCC patients with stage II and III disease in the National Cancer Database (NCD) and found patients with stage III (as compared to lower stage II disease) and poorly differentiated or undifferentiated tumors were more likely to receive standard therapy [42].…”
Section: Discussionsupporting
confidence: 90%
“…Racial disparities in receipt of standard treatment has been shown in numerous cancers, including breast, prostate, lung, gynecologic, and gastrointestinal cancers ( 1 , 16 - 20 ). In a SEER analysis evaluating breast, non-small cell lung, and prostate cancer, Black patients were less likely to receive guideline concordant treatment than White patients, and mortality risks were lowered after adjusting for standard treatment ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a SEER analysis evaluating breast, non-small cell lung, and prostate cancer, Black patients were less likely to receive guideline concordant treatment than White patients, and mortality risks were lowered after adjusting for standard treatment ( 19 ). In an NCDB study evaluating standard treatment for locally advanced anal squamous cell carcinoma, racial survival differences that were present between Black and White patients were rectified in the subgroup that received standard treatment ( 20 ). In summation, these studies emphasize the importance of eliminating barriers to receipt of standard treatment to decrease racial disparities of standard treatment and survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Larger studies have focused on some of the socioeconomic factors such as median household income, race, or sex. [13][14][15] A large US study describing the effect of various socioeconomic determinants, such as income, race, insurance status, education level on treatment delay, and survival, is lacking in the literature.…”
Section: Desigualdades Socio-económicas En Casos De Cáncer Anal: Efec...mentioning
confidence: 99%